Applications of Engineering Techniques in Microvasculature Design - Al Halawani, Aleen; Wang, Ziyu; Liu, Linyang; Zhang, Miao; Weiss, Anthony S. (Frontiers in Cardiovascular Medicine, 2021)
Achieving successful microcirculation in tissue engineered constructs in vitro and in vivo remains a challenge. Engineered tissue must be vascularized in vitro for successful inosculation post-implantation to allow instantaneous perfusion. To achieve this, most engineering techniques rely on engineering channels or pores for guiding angiogenesis and capillary tube formation. However, the chosen materials should also exhibit properties resembling the native extracellular matrix (ECM) in providing mechanical and molecular cues for endothelial cells. This review addresses techniques that can be used in conjunction with matrix-mimicking materials to further advance microvasculature design. These include electrospinning, micropatterning and bioprinting. Other techniques implemented for vascularizing organoids are also considered for their potential to expand on these approaches.